1977
DOI: 10.1088/0022-3727/10/18/015
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of saw-tooth domain walls in Ni/Fe/Co films

Abstract: Head-on domains having saw-tooth wall configurations in Ni/Fe/Co films are discussed in relation to the existing theoretical models. The existence of Neel tails within such wall structures as previously proposed is supported and discussed with respect to: (a) direct magneto-optic observations and measurements, and (b) a comparison of the predicted saw-tooch amplitude and angles with the observed values. A large number of films were investigated and the wall angles were found to be dependent upon the ratio of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…32. The calculation is based on a Néel tail transition model 33 which involves an in-plane magnetization rotation over a transition region: the spins rotate following the wall shape. Thus the entire region surrounding the wall exhibits a nonuniform magnetization ͑see Fig.…”
Section: Energetics Of Zigzag Domain Wallsmentioning
confidence: 99%
“…32. The calculation is based on a Néel tail transition model 33 which involves an in-plane magnetization rotation over a transition region: the spins rotate following the wall shape. Thus the entire region surrounding the wall exhibits a nonuniform magnetization ͑see Fig.…”
Section: Energetics Of Zigzag Domain Wallsmentioning
confidence: 99%
“…Some authors have found a strong relationship between the characteristic parameters of the zigzag walls and the macroscopic magnetic properties, such as coercitivity (or nucleation magnetic field) and anisotropy fields (although the coercitivity is not an intrinsic material property, it is an important parameter in magnetic recording media). Sanders et al [25], according to the model proposed by Minnaja and Nobile [38], found a dependence of the angle θ on the ratio of H c /H k , where H c is the coercive field and H k is the in-plane uniaxial anisotropy field, for NiFeCo films with thicknesses between 50 and 190 nm. They also found a dependence of the zigzag amplitude 2B on the coercive field, in a similar way to that found in the work of Dressler and Judy for high-coercivity Co and CoCr films with thicknesses between 10 and 70 nm [24], but the experimental values for 2B of Sanders et al were not in quantitative agreement with the values deduced from the model of [38].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the film thickness, the core corresponds to Bloch, cross-tie or Néel walls. These zigzag domain walls have been observed in many different systems: for example, in evaporated, amorphous, ferrimagnetic GdCo and sputtered GdFeB films [20]; SmCo amorphous films [21]; permalloy coated garnets [22]; GdFe amorphous films [23]; evaporated, polycrystalline, highly-coercive Co and CoCr samples [24]; Ni/Fe/Co multilayers [25]; ion-implanted garnet structures [26]; NiO/Co bilayers sputtered at oblique incidence [27]; MnAs thin films [28][29][30]; exchange-biased NiO/NiFe bilayers [31]; permalloy films [32]; trilayers combining hard magnetic/non-magnetic/soft magnetic layers, such as Co/Al 2 O 3 /FeNi [33]; epitaxial Fe films grown on GaAs(001) [34] and (La, Sr)MnO 3 epitaxial thin films [35]. The scientific and technological interest of some of these magnetic structures centres on their use in memory devices, spin-valve structures (in the case of exchange-coupled films), spintronic applications, magnetoresistive sensors in the case of permalloy films or magnetic tunnel junctions.…”
Section: Introductionmentioning
confidence: 99%
“…1͑b͔͒. 5 The saw-tooth domains are indications of increasing disorder, which exhibits itself as an increase in hysteresis when shifting from north-south to south-north magnetic fields. the same sample stub holding the permalloy film.…”
mentioning
confidence: 99%